2000
DOI: 10.1002/(sici)1099-0860(200002)14:1<37::aid-chi564>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Adversity, resilience and young people: the protective value of positive school and spare time experiences

Abstract: This paper argues for the value of resilience as a key concept in work with young people in need and considers some of the implications of a resilience led approach for policy and practice. Resilience refers to a capacity to do well despite adverse experience. Social and developmental factors influencing a child or young person's degree of resilience are discussed, with particular reference to the resilience enhancing potential of school experiences and spare time activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 7 publications
4
41
0
4
Order By: Relevance
“…Children and young people were often involved in significant decisions affecting their lives and those of their family, demonstrating their capacity to actively engage in dealing with adversity. This supports the potential for children to develop a sense of self efficacy [12] and to be 'competent survivors', a term used in relation to armed conflict [26]. It is also consistent with the model of the 'citizen child', described in the sociology of childhood, as being capable of contributing to decisions affecting their lives, a right enshrined in the UN Convention on the Rights of the Child [16,28,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children and young people were often involved in significant decisions affecting their lives and those of their family, demonstrating their capacity to actively engage in dealing with adversity. This supports the potential for children to develop a sense of self efficacy [12] and to be 'competent survivors', a term used in relation to armed conflict [26]. It is also consistent with the model of the 'citizen child', described in the sociology of childhood, as being capable of contributing to decisions affecting their lives, a right enshrined in the UN Convention on the Rights of the Child [16,28,36].…”
Section: Discussionmentioning
confidence: 99%
“…While most disaster survivors will recover without the need for specialised support [5,11], post-disaster community interventions to support positive outcomes are important for reducing the risk of serious problems arising in multiple areas of a child or young person's life with detrimental consequences for critical developmental functions [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly concerning as the capacity/likelihood of social support is a significant protective factor in mental illness (Gilligan, 2000;Hall-Lande et al, 2007;Ravens-Sieberer, 2008;Steinhausen & Metzke, 2001). Studies undertaken from a range of perspectives have noted the importance of social networks, yet it remains a relatively under-developed area of research and practice in relation to children and adolescents who experience child maltreatment (Frederico, Jackson, & Black, 2006).…”
Section: Child Maltreatment and Social Supportmentioning
confidence: 99%
“…Smokowski, Reynolds, and Bezruczko (2000) found that transitional events appeared to be crucial times when vulnerable young people were particularly susceptible to changing their behaviour positively or negatively. Gilligan (2000) emphasises the importance of supportive pathways and turning points in development for children suffering from multiple disadvantages: "One favourable experience may be a turning point in a child's or young person's trajectory of development" (p. 39). Finally, there is evidence to suggest that positive educational experiences may contribute to the more general resilience of children in care.…”
Section: Introductionmentioning
confidence: 98%